Evaluation of Thermal Comfort in Argo Lawu New Generation Train Using Transient CFD Simulation - F. Ananta; T.J. Saputra; N.D. Fajarningrum (Universitas Mataram, 2025)
Thermal comfort is one of the key aspects in providing quality passenger service in railway transportation. This study aims to analyze the performance of the air conditioning system in the Argo Lawu New Generation train coach using time-based Computational Fluid Dynamics (CFD) simulation transient. The simulation was conducted on two air conditioning configurations: KA 1 (AC units at both ends of the coach) and KA 2 (a single AC unit at the center of the coach). The simulation process consists of three main stages: pre-processing, processing, and post-processing. It was performed for 180 seconds with a 1 second time interval to observe dynamic changes in temperature distribution, air velocity, and pressure. The results show that KA 2 provides a more uniform distribution of temperature and airflow, with a final average temperature of 24.8°C compared to 25.1°C in KA 1. The central placement of the AC unit proves to be more effective in maintaining balanced pressure and distributing cool air throughout the cabin. This transient CFD simulation offers a more realistic representation of the cooling system’s performance and serves as a reference for future train HVAC design improvements.